ANALISIS DISTRIBUSI SUHU DAN EFISIENSI TERMAL PADA OVEN PENGERING LISTRIK KAPASITAS 3 KG - Ridho Fadhil Romadhon; Dianta Mustofa Kamal (Jurnal Mema (Jurnal Mesin dan Manufaktur), 2025)
This study aims to analyze the temperature distribution and thermal efficiency of a 3 kg capacity electric drying oven used for drying elephant ginger (Zingiber officinale var. officinarum). The oven model was designed using SolidWorks 2020, then a Computational Fluid Dynamics (CFD)-based thermal analysis was performed using ANSYS Fluent 2021. This oven design refers to the hybrid oven model from Hutajulu's research [21]. Simulations were carried out at an operating temperature of 60°C to determine the heat distribution pattern, air flow, and heat transfer efficiency between oven components. The simulation results showed that the average temperature of the drying chamber ranged from 55–60°C with a maximum deviation of 5°C and a thermal efficiency of 76.63%. Compared to traditional drying methods which take 3–11 days and depend on the weather [3], this electric oven is able to reduce the moisture content of elephant ginger from 80–85% to below 10% in just 7–9 hours. With high temperature stability and energy efficiency, this oven is considered more hygienic, fast, and effective for application in the biopharmaceutical plant-based home industry.